The CQ Press guide to radical politics in the United States - Burgess, Susan 1961-; Leeman, Kate (CQ Press, 2016)
The CQ Press Guide to Radical Politics in the United States is a unique work which provides an overview of radical U.S. political movements on both the left and the right sides of the ideological spectrum. It focuses on analyzing the origins and trajectory of the various movements, and the impact that movement ideas and activities have had on mainstream American politics. This guide is organized thematically, with each chapter focusing on a prominent arena of radical activism in the United States. These chapters will: • Trace the chronological development of these extreme leftist and rightist movements throughout U.S. history • Include a discussion of central individuals, organizations, and events, as well as their impact on popular opinion, political discourse, and public policy • Include sidebar features to provide additional contextual information to facilitate increased understanding of the topic Seeking to provide an accessible, balanced, and well-documented discussion of topics often overlooked in political science, this book includes an introduction to anarchism, communism, and socialism as well as the Chicano movement, civilian border patrols, Black power, the Ku Klux Klan, ACT-UP, the militia movement, Occupy Wall Street, farmers' rebellions, Earth First!, the Animal Environmental Liberation Front, and many others